2017
DOI: 10.1515/geochr-2015-0077
|View full text |Cite
|
Sign up to set email alerts
|

Post-IR IRSL dating of K-feldspar from last interglacial marine terrace deposits on the Kamikita coastal plain, northeastern Japan

Abstract: Abstract:To establish a suitable luminescence dating protocol for marine terrace deposits in Japan, we tested the applicability of K-feldspar post-infrared (IR) infrared stimulated luminescence (IRSL) (pIRIR) dating using a marine isotope stage (MIS) 5e terrace deposit from the Kamikita coastal plain (NE Japan), where independent age control from a tephra is available. One of the most commonly used pIRIR signals, measured at 290°C with the first IR stimulation temperature at 50°C (pIRIR 50/290 ), faded with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Especially with luminescence dating of feldspar, considerable progress has been made in the last 10 years in searching for long‐term stable signals. For example, consistent ages in accordance with independent dating results could be achieved using the pIRIR method (Thomsen et al ., ; Buylaert et al ., ; Ito et al ., ; Klasen et al ., ; see Li et al ., for an overview), although there still seem to be methodological challenges in the age range >100 ka (e.g. Lowick et al ., ; Lomax et al ., ).…”
Section: Discussionmentioning
confidence: 87%
“…Especially with luminescence dating of feldspar, considerable progress has been made in the last 10 years in searching for long‐term stable signals. For example, consistent ages in accordance with independent dating results could be achieved using the pIRIR method (Thomsen et al ., ; Buylaert et al ., ; Ito et al ., ; Klasen et al ., ; see Li et al ., for an overview), although there still seem to be methodological challenges in the age range >100 ka (e.g. Lowick et al ., ; Lomax et al ., ).…”
Section: Discussionmentioning
confidence: 87%
“…The equivalent dose ( D e ) of the samples were measured using elevated temperature post-IR IRSL (pIRIR), stimulated at 290°C after preheating at 320°C for 60 s and with the first IR stimulation at 200°C. By increasing the first stimulation temperature from the standard 50°C (Thiel et al, 2011) to 200°C, the signal can be considered to be free from anomalous fading (e.g., Ito et al, 2017). Ten aliquots each were measured for samples PHD1–6, and six aliquots were measured for GWD1–2 and TRG1–2.…”
Section: Methodsmentioning
confidence: 99%
“…Stevens et al [89] reported that D e values were underestimated when the prior-IR stimulation temperature was below 140 • C, but a D e plateau had been reached when the prior-IR stimulation temperature was ≥170 • C; and the pIRIR 200, 290 protocol was adopted to date the Chinese loess back to the S2 layer (second paleosol layer, corresponding to MIS 7). Ito et al [29] carried out prior-IR stimulation temperature test on marine terrace deposits from Japan, and the results showed that the pIRIR 290 D e plateau existed when the prior-IR temperature was within the range of 100-200 • C; while the pIRIR 290 D e was underestimated with a prior-IR temperature of 50 • C and overestimated with a prior-IR temperature of 250 • C. A study performed on rock slices showed that the pIRIR 290 signal from naturally saturated slices was close to the laboratory saturation level only when the first-IR stimulation temperature was high (e.g., 200 • C or 250 • C) [81]. These studies suggest that the first-IR stimulation is better to be performed at a higher temperature (e.g., 200 • C) when dating older samples with the pIRIR 290 signal.…”
Section: Comparison Between Different Pirir Protocolsmentioning
confidence: 99%
“…The minimal residual dose of the pIRIR 50, 225/290 signal is mostly in the range of 4-7 Gy, which represents the contribution of an un-bleachable component that ubiquitously exists in fully-bleached samples [39,49,50,[52][53][54]. In addition, some studies showed that with extremely long bleaching durations, the residual doses were also reduced to <10 Gy [29,51,52]. In summary, the residual doses of pIRIR 290 signal for partially-bleached sediments (e.g., glaciofluvial deposits) could be high (up to~50 Gy), but the residual doses for well-bleached sediments are, in most cases, smaller than 10 Gy.…”
Section: Two-step Ir Stimulationmentioning
confidence: 99%
See 1 more Smart Citation